Incidencia de la mano de obra no calificada en la producción de viviendas de interés social en la ciudad de Loja. - Rodríguez León, Jorge Alberto (2011)
The current conditions of global instability, product of an accelerated process of environmental degradation, have raised the need to substantially improve the quality control processes in the construction of buildings designed for man. When factors such as earthquakes, wind, sun and abnormal and recurrent rainfall affect buildings, it becomes extremely important to meet minimum quality standards in construction. Hence, this research is intended to address an issue which building contractors, owners, government agencies, etc., face every day while carrying out their duties: the lack of skilled labor for the construction of civil engineering and architectural structures. This problem will become more serious over time if measures that allow the training of the workforce involved in the housing industry are not implemented. This work is divided in two parts: - The first part measures the quantitative impact of labor in the construction of social housing in Loja. Moreover, it quantifies the actual performance of the local labor in the most important areas included in the total cost of housing. This information is then used to determine the referential direct costs of the aforementioned areas and therefore the referential direct cost of social housing, as well as the impact of labor on the total cost of housing. - The second part deals with the qualitative analysis of the incidence of labor in the construction of social housing. These results led to identify the main defects found in the social housing project “Ciudad Victoria”, built by the Empresa Municipal de Vivienda, in Loja. These outcomes will serve as benchmarks for improving the technical quality in the construction of housing. A manual of recommendations is additionally presented in order to prevent and correct the most frequent errors and failures in the housing construction process. To conclude, the recommended solutions seek to present a valid alternative for the creation of a public school of training and certification for construction workers in Loja.